The Impact of the Recent Global Financial Crisis on Deal Structures of Mergers & Acquisitions from a Malaysian Perspective - Abu Hassan Shaari, Fazlin (2010)
The perceived slowdown in the number of mergers and acquisitions (“M&As”) within the Malaysian landscape poses contradictory arguments. Sluggish conditions would logically be an opportunity for least affected companies which are cash rich to embark on an expansion phase or companies with low leverage to potentially gear up to grow through M&As. However, the perception of depressed valuations may not necessarily prompt an influx of M&A activities, as sentiments and liquidity constraints may hinder expansion vibes. Past studies on M&As tend to focus on the value creation/ destruction properties, the execution/ integration challenges and market reaction/ wealth creation pursuant to deal announcements. There is a gap in literature in terms of whether there is a difference in undertaking expansion through M&As during a market down-cycle such as the recent global financial crisis. This study attempts to analyse M&A deal structure differences, assessed from a general overview of transaction quantum , strategy (seen from industry participation, rationale and cross-border transactions) and valuation basis (with emphasis on price-earnings (“PE”) and price book (“PB”) multiples); with a focus on the mode of settlement of purchase consideration and the corresponding signalling properties. The research methodology adopted is a mixture of both quantitative and qualitative research methods, based on information contained in Circulars to Shareholders released to the local Exchange (“Circulars”) and a survey questionnaire targeted at M&A practitioners. The perceived differences between the general modes of settlement post-crisis are not found to be statistically significant. Although the differences across the low, mid and high range transaction values are found to be statistically significant, they do not provide conclusive support that the higher the transaction size, the higher the use of share settlement. Only 3 signalling properties are supported by the survey findings i.e. acquirers’ careful deliberation of the effects of share deals in view of internal/ external implications, the positive relationship between strong valuation of acquirer shares and the likelihood of share issuance and the reduction in the proportion of post-crisis cash acquisitions financed by borrowings. On valuation, intrinsic value and fair value are found more prevalent post-crisis. Although the average PE & PB multiples increase in the post-crisis sample, only the PB multiples changes appear to be statistically significant. M&A rationale mostly cited in the Circular/ survey appear to be market share growth, core competences enhancement, industry consolidation and related diversification. Resources-based, infrastructure and financial services industries’ dominance of the M&A pie appear to be growing at the expense of GDP-sensitive sectors. Inbound international M&As have about doubled in transaction share mainly in strategic industries whilst a 3% share increase is noted for outbound M&As particularly for heavy industries, telecommunications, industrial and consumer products sectors. By understanding the differences (or otherwise) of the findings with respect to a few aspects of deal structures compared to expectations, it is hoped that the perspective of Malaysian companies with regards to the pursuance of M&A activities during market slowdown is understood, as a general guide for academics and practitioners to understand the relevant market dynamics, going forward.